2008
DOI: 10.1007/s12111-008-9046-5
|View full text |Cite
|
Sign up to set email alerts
|

“We Didn’t Get Nothing:” The Plight of Black Farmers

Abstract: The central thesis to this article is that blacks were intended to work the land, but never to own the land. The progression from working the land via slavery, to peonage, and to land ownership is explored. Africans arrived on American soil carrying with them a rich legacy in caring for the land, and while they did so in America, it was under the most onerous of conditions. Once freed, blacks became prodigious land owners, but with the onset of the twentieth century various systemic factors impacted landowners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 7 publications
(5 reference statements)
2
24
0
Order By: Relevance
“…In the era of slavery, White landowners sought the expertise of African slave farmers to improve crop cultivation, production, and animal husbandry (Hinson & Robinson, 2008). After the Civil War the number of African American farmers proliferated, peaking in 1920, when nearly 926,000 individuals worked farms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the era of slavery, White landowners sought the expertise of African slave farmers to improve crop cultivation, production, and animal husbandry (Hinson & Robinson, 2008). After the Civil War the number of African American farmers proliferated, peaking in 1920, when nearly 926,000 individuals worked farms.…”
Section: Introductionmentioning
confidence: 99%
“…The initial decrease in African American-operated farms is attributed to increased farm mechanization and the end of the sharecropping system (Wood & Gilbert, 2000). Recent factors associated with the decline in the number of African American farmers are argued to be not the result of economic trends alone, and to include: structural changes by U.S. agriculture favoring large farms, cumbersome tax laws, mortgage foreclosures, intestate death of landowners in the absence of a will and the resulting partition sales, and discrimination (Brown, Christy & Gebremedhin, 1994;Gilbert, Sharp, & Felin, 2002;Hinson & Robinson, 2008). Discriminatory lending practices on the part of the U. S. Department of Agriculture (USDA) included not providing African American farmers with access to credit, granting less credit to African American farmers than White farmers, and distributing loans to African American farmers too late in the farming season for maximized farming production (Gilbert, Sharp, & Felin, 2002;Hinson & Robinson, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly during the second half of the 20 th century, smaller farms struggled to keep up with the cost of mechanization, more complex inputs (e.g., fertilizers, pesticides, new cultivars), and the need to purchase additional acreage to capture ever-greater economies of scale. This struggle to compete at increasing scales was systematically greater for African American farmers than for White farmers (Hinson & Robinson, 2008). Over the last century, the country experienced an estimated 98 percent loss in African American farm operations and a 66 percent loss in White farm operations, all while the largest (and typically White-owned) farming operations grew even larger (Green et al, 2011).…”
mentioning
confidence: 99%
“…In 1982, a U.S. Civil Rights Commission found that in 1980 and 1981 local offices of the USDA loaned less than two percent of all farm ownership loan amounts and less than three percent of all farm operating loan amounts to African American farmers (Hinson & Robinson, 2008). As a result, the largest class action lawsuit in U.S. history, known as the Pigford case, was filed against the U.S. Department of Agriculture in the late 1990s and was settled in 2000, resulting in ongoing claims processing for African American, Hispanic, Native American, and women ranchers and farmers (Hinson & Robinson, 2008). 2 The loss of farm land ownership pushed many African Americans into urban spaces, migrations reflected in many central cities that are now home to large African American populations (Green et al, 2011;Massey & Denton, 1993).…”
mentioning
confidence: 99%